Phân cấp tài khóa và tăng trưởng kinh tế: Tổng hợp lý thuyết và đề xuất hướng nghiên cứu tiềm năng - Đặng Thị Bạch , Vân; Bùi Duy , Tùng; Nguyễn Quang , Bình (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2020)
The study aims to investigate the relationship between fiscal decentralisation and economic growth by reviewing, consolidating and grouping of related literature. To be more specific, the paper analyses the past literature on fiscal federalism to highlight its drawbacks. Then, the study discusses future research implications relating to examining possible endogenous transmission channels of the relationship between fiscal decentralization and economic growth on three main areas: (i) Fiscal decentralization – Human capital/Social capital – Growth; (ii) Fiscal decentralization – Endogenous technology – Growth; and (iii) Fiscal decentralization – Sustainability – Institutions – Politics – Market-preserving federalism – Growth.